A comparison of reciprocal teaching and scientific approaches for improving pupils' mathematical understanding - Dina Apryani; Rambat Nur Sasongko; Muhammad Kristiawan; Nurul Astuty Yensy B.; Hidayatulloh Hidayatulloh (Jurnal Elemen, 2022)
This study is intended to result in instruction that will help pupils improve their mathematics understanding skills. The similarity of strategies in both the scientific and reciprocal teaching approaches makes it difficult to choose which approach is better. This investigation aims to investigate and explain (1) Improving pupils' mathematical understanding through comparison of scientific approaches and Reciprocal Teaching based on PAM; (2) The impact of the interaction between learning approaches with pupils' PAM on enriching pupils' mathematics understanding ability. It is a quasi-experimental research project that uses two experimental classes. The results of this study are (1) Pupils who learn through the scientific approach and pupils who learn through reciprocal teaching strategies based on PAM pupils have different mathematical thinking abilities, with the average value of improvement in the scientific approach class being more significant than the reciprocal teaching approach class; (2) Learning and pupils' PAM have no interaction effect. It means that learning in both experimental classes applies to all pupils overall in improving pupils' mathematical understanding ability. Based on the results of this study, this study implies that teachers can employ learning using a scientific approach as one of the learning options for pupils to increase their mathematical understanding abilities.